What is the Prevalence of General Anxiety Disorder and Depression Symptoms in Semi-elite Australian Football Players: A Cross-Sectional Study - Anthony Henderson; Sarah Ann Harris; Troy Kirkham; Jonathon Charlesworth; Myles Calder Murphy (SpringerOpen, 2023)
Abstract Background The prevalence of anxiety and depression symptoms in semi-elite Australian footballers is unknown. The primary objective of this study was to determine the prevalence of generalised anxiety disorder (GAD) and depressive symptoms in semi-elite Australian Football players. Our secondary objective was to explore the association between demographic and football-specific factors with GAD and depressive symptoms. A cross-sectional epidemiological study including 369 semi-elite Western Australian Football League (WAFL) players from the Men and Women's 2022 season (n = 337 men, 91%) was conducted. Symptoms of depression were measured using the Patient Health Questionnaire-9 scale (PHQ-9) and symptoms of GAD with the GAD-7 scale. Results Our response rate was 82.9%. Thirteen players had missing data. The prevalence of GAD symptoms was 8.5% in men and 28.6% in women (10% overall). The prevalence of depressive symptoms was 20% in men and 57% in women (23% overall). Being a woman (gender) was associated with a sevenfold increased risk of GAD and/or depression symptoms [odds ratio (OR): 7.33, 95% confidence interval (CI): 3.18-16.92; p < 0.001]. Players of 'Aboriginal or Torres Strait Islander' ethnicity were two times more likely to report GAD and/or depression symptoms in comparison to players of 'Australian' ethnicity (OR: 2.13; 95% CI: 1.01-4.49; p = 0.048). Concussion history was not a significant risk factor for GAD or depression symptoms. Conclusion This study demonstrated that approximately 1 in 10 WAFL players met the diagnostic cut-off criteria for probable GAD, and 1 in 5 for probable depression. The prevalence for depression symptoms in this study were far higher than the national average in the comparative age bracket. WAFL women's players also reported a substantially higher prevalence of GAD and depressive symptoms than men, and should be further investigated as a priority by the WAFL.